Three-Rooted Permanent Mandibular First Molars: A Meta-Analysis of Prevalence - Nyan M. Aung; Kyaw K. Myint (Hindawi Limited, 2022)
Introduction. Although numerous amounts of high-level evidence were present, they solely emphasized the tooth-level prevalence of three-rooted permanent mandibular first molar. Global patient-level prevalence and bilateral symmetrical distribution of this type of teeth were needed to be tackled across the world. The research question was "What is the global prevalence of three-rooted permanent mandibular first molars?" Materials and Methods. In vivo epidemiological studies undergone with Cone Beam Computed Tomography (CBCT) were eligible. The proportions of the prevalence of three-rooted permanent mandibular first molars were presented in the forest plots by random effect model. The calculation was performed with MetaXL version 5.3. Subgroup analysis, sensitivity analysis, and publication bias method were also calculated. Results. Seventy-two studies from 31 countries were selected for both qualitative and quantitative analyses. 26302 patients and 37994 permanent mandibular first molars were included in the analysis. 9% of permanent mandibular first molars all over the world demonstrated 3 roots. These three-rooted teeth were found in 10% of the world population, more than 45% of which revealed bilateral symmetry of that anatomy. Right-side dominance and no sexual dimorphism were seen in the distribution of three-rooted permanent mandibular first molars. Global tooth-level prevalence of Radix Entomolaris and Radix Paramolaris was 12% and 0.1%, respectively. Conclusion. The prevalence of three-rooted permanent mandibular first molars (PMFMs) was influenced by different geographical locations across the world and also by widespread habitation of the Mongoloid descent. The authors postulate that globalization, together with blending among ethnicities, may have a great impact on the reduction or accentuation of the anatomical significance in some populations.